PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANIMASI PADA MATA PELAJARAN DESAIN KOMUNIKASI VISUAL DI SMK NEGERI 1 SITIUNG - Livia Agustin; Thomson Mary; Faiza Rini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The problems that exist in print graphic design subjects, especially in the material of applying typography according to the media, are not yet available,  learning media based on animation, so that students find it difficult to understand the material during the learning process. This study aims to develop valid and practical animation-based  learning media. This study uses the Research and Development method with the ADDIE development model. The subjects of this study were 15 students. Data collection techniques using a Likert scale questionnaire. The data analysis technique in the development of animation-based learning media is quantitative. The results of this study show that the average value of the media expert's validity test is 0.85% with the valid category and 0.92% for the media expert with the valid category. For the practicality test on the teacher's response it reached 93,56% in the very practical category and for student responses it reached 84,67% in the very practical category. Conclusions and results of field trials of animation-based  learning media have been tested for feasibility and can be used as learning media for printing graphic design.